Inhibition of dengue NS2B-NS3 protease and viral replication in Vero cells by recombinant retrocyclin-1 - Rothan Hussin A (BMC Infectious Diseases, 2012)
Abstract Background Global resurgence of dengue virus infections in many of the tropical and subtropical countries is a major concern. Therefore, there is an urgent need for the development of successful drugs that are both economical and offer a long-lasting protection. The viral NS2B-NS3 serine protease (NS2B-NS3pro) is a promising target for the development of drug-like inhibitors, which are not available at the moment. In this study, we report retrocyclin-1 (RC-1) production in E. coli as a recombinant peptide to test against dengue NS2B-NS3pro. Methods Dengue NS2B-NS3pro was produced as a recombinant single chain protein in E. coli and purified by Ni+ affinity chromatography. The RC-1 peptide was produced in E. coli and the tri-disulphide bonds were reformed in a diluted alkaline environment. Protease assay was performed using a fluorogenic peptide substrate and measured by fluorescence spectrometry. Real-time PCR was used for quantification of dengue serotype 2 (DENV-2) viral RNA produced in Vero cells. Results The RC-1 peptide inhibited the activity of recombinant NS2B-NS3pro with different values at 50% inhibitory concentration (IC50) which are temperature dependent (28°C, 46.1 ± 1.7 μM; 37°C, 21.4 ± 1.6 μM; 40°C, 14.1 ± 1.2 μM). The presence of RC-1 significantly reduced viral replication in Vero cells infected with DENV-2 at simultaneous treatment after 48 hrs (70%) and 75 hrs (85%). Furthermore, moderate reduction in viral replication was observed at pre-treatment mode after 48 hrs (40%) and 72 hrs (38%) and post-treatment at 48 hrs (30%) and 72 hrs (45%). Conclusion Recombinant RC-1 inhibits DENV-2 replication in Vero cells by interfering with the activity of its serine protease. Thus, we propose that recombinant RC-1 is a potent, cost-effective dengue virus inhibitor. Therefore, it is suitable to consider RC-1 as a new candidate for drug development against dengue infection.